The interactive effects of extrinsic and intrinsic motivations on service recovery performance: the mediating role of self-efficacy - Yanni Zhu; Yixuan Wang; Baoyi Song; Qiaoyan Feng; Huiying Lin; Juan Tang (Tourism & Management Studies)
In recent decades, interest has grown in understanding the mechanisms of service recovery performance (SRP) in the hospitality industry. This study introduces an interactive perspective incorporating both extrinsic and intrinsic factors, investigating the roles of inclusive leadership and job autonomy on employee self-efficacy, with self-efficacy mediating their relationships with SRP. Surface acting is proposed as a negative moderator. A sample of 83 supervisors and 350 frontline employees from 8 Chinese hotels completed questionnaires. Data analysis was conducted using PLS-SEM in Smart PLS 4 and regression analysis in SPSS 25. Results show that inclusive leadership and job autonomy contribute to strong self-efficacy and enhanced SRP. Surface acting moderates the relationship between inclusive leadership and self-efficacy but not between job autonomy and self-efficacy. This cross-sectional survey offers practical implications for hospitality managers, providing guidance on fostering environments that promote self-efficacy and enhance SRP. Limitations include reliance on self-reported measures and a cross-sectional design. Future research could explore other moderators and mediators, different industries, and use longitudinal or experimental designs to establish causality.